Construire un outil d’association de données à l’heure de l’open data : La Fabrique Numérique du Passé (FNP) - Laurent Costa (Les Cahiers de l'École du Louvre)
Like Gaignières in his day, current trends and public policies to open up data are re-examining the mechanisms for collecting, making available and exploiting bodies of information that are now digital. Data hubs are being set up, multiform collections developing both locally in France and internationally. These objects, now known as data warehouses, are not neutral and will determine the landscape of heritage research in the future. The aim of this paper is to examine these objects, whose technical dimension and interfaces play a major role. It will also look at the extent to which, as in the case of the Gaignières collection, these tools influence the dynamics of our knowledge. To illustrate this, we will be using a new tool that we hope to put into perspective: the open data platform La Fabrique Numérique du Passé. La Fabrique Numérique du Passé (FNP), an open data platform for geohistorical data, has set itself the goal of developing accessible tools for the sciences of heritage and the past to capitalise on and make available data, in accordance with the principles of open data and fair data. FNP is aimed at research players, enabling them to get involved in a simple process of opening up data as part of the wider open science movement (ouvrirlascience.fr). More functionally, the aim is to bring together existing information and make the data produced as part of research projects and programmes (PCR, ANR, ERC, etc.) available for free download in the most “accessible” standard format so that it can be easily reused by all socioeconomic players and local stakeholders. The FNP is a way of bridging the gap for our disciplines between permanent repositories (data warehouses such as Nakala for the humanities and social sciences), players who produce data as part of research projects and a pool of data that needs to be both durable and accessible so that it can be mobilised by new players.